Kinetic Study of Blue Methylene Adsorption Using Coconut Husk Base Activated - Baunsele, Anselmus Boy; Boelan, Erly Grizca; Kopon, Aloisius Masan; Rahayu, Rahayu; Siswanta, Dwi (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2022)
Blue methylene is a cationic dye. It is usually as in various industries. The waste of blue methylene can reduce the environmental balance, especially for aquatic biota, by inhibiting the penetration of sunlight into the water. The experiment used the most natural ingredients and methods to minimize the existence of the dye. In this research, coconut husk was activated with NaOH solution and then used for blue methylene adsorption. The coconut husk started aims to reduce the pollution of the adsorbent to increase the adsorption capacity. The study result showed the optimum adsorption of blue methylene at pH 7 for 75 minutes of adsorption with the capacity adsorption of 1.41 mg g-1. The development of the kinetic study described the adsorption process according to a second-order pseudo reaction kinetic model with the constant adsorption rate of 2.54 x 10-4 g mg-1 minute-1.